On Non-Linear Finite State Digital Channel Coding - Hermawan Kresno Dipojono (Institute for Research and Community Services (LPPM) ITB, 1987)
Abstract. A discrete-time digital channel coding, in which the encoder and decoder are both time-invariant finite state machines, is investigated. The channel is assumed to be memoryless. Two measures of performance are considered: the probability of error and the minimum free distance. Greater emphasis is placed on the minimum free distance since it is easier to evaluate than the probability of error criterion, and for small channel crossover probability it is a very good indicator of system performance; it is defined as the Hamming distance between two possible output sequences that correspond to distinct state sequences of the same length that are identical at both the start and finish. An algorithm to calculate the distance between such possible output sequences was developed; it also identifies all such pain of output sequence. Another algorithm, based on the finite state machine properties of the encoder, was found to generate the finite state decoder. Finally, after having found the pairs of encoder-decoder finite state machines, we simulated the communication system. Sari. Suatu kode saluran digital dengan waktu tercacah yang mempunyai pasangan encoder-decoder berupa mesin berkeadaan terhingga dan invarian waktu akan diteliti. Saluran dianggap tanpa daya ingat. Digunakan dua buah ukuran kinerja yaitu probabilitas kesalahan dan jarak bebas minimum. Penggunaan jarak bebas minimum lebih ditekankan karena lebih mudah dievaluasi dibandingkan probabilitas kesalahan. Untuk probabilitas kesalahan saluran yang kecil, jarak itu merupakan indikator yang sangat baik bagi kinerja sistem; ia didefinisikan sebagai jarak Hamming minimum antara dua buah kemungkinan sekuen keluaran yang berupa sekuen keadaan yang unik dengan panjang dan keadaan yang sama, baik di awal maupun di akhir sekuen. Sebuah algoritma untuk menghitung jarak antara sekuen keluaran yang sedemikian itu telah pula dikembangkan; algoritma tersebut juga mampu mengidentifikasi semua pasangan sekuen keluaran itu. Sebuah algoritma lainnya, didasarkan pada sifat-sifat encoder sebagai mesin dengan keadaan berhingga, yang mampu menyusun decoder dengan keadaan berhingga, telah pula ditemukan. Akhirnya, setelah menemukan berbagai pasangan encoder-decoder yang berupa mesin dengan keadaan berhingga, sistem komunikasi digital disimulasikan.